MANAJEMEN SARANA DAN PRASARANA PEMBELAJARAN BERDASARKAN STANDAR NASIONAL - Hajrawati, Hajrawati (Pascasarjana Universitas Negeri Makassar, 2013)
The studyaimed at discovering thedescription of themanagementof facilities and infrastructure of learning based onnational Standard at SMKN 1 in Jeneponto. The resultsof the study revealed that the management of facilities and infrastructure at SMKN 1consisted of (1) the managementof facilities and infrastructureof learning,(2) The standardization of facilities and infrastructure had not been appropriate in supporting a better learning prosess based, and(3) the in hibiting factors of the procurement of facilities and infrastructure were lack of fund to fulfill the needs of facilities and infrastructure and limited land which could be used as a place to store the facililities to be used; whereas the supporting factors were the students and teachers which could be used asthe reason to have the facilities and infrastructure as well as the funding.